Little impact of the Three Gorges Dam on recent decadal lake decline across China's Yangtze Plain. Issue 5 (11th May 2017) - Wang, Jida; Sheng, Yongwei; Wada, Yoshihide
Abstract: The ubiquitous lakes across China's Yangtze Plain (YP) are indispensable freshwater resources sustaining ecosystems and socioeconomics for nearly half a billion people. Our recent survey revealed a widespread net decline in the total YP lake inundation area during 2000–2011 (a cumulative decrease of ∼10%), yet its mechanism remained contentious. Here we uncover the impacts of climate variability and anthropogenic activities including (i) Yangtze flow and sediment alterations by the Three Gorges Dam (TGD) and (ii) human water consumption in agricultural, industrial, and domestic sectors throughout the downstream Yangtze Basin. Results suggest that climate variability is the dominant driver of this decadal lake decline, whereas studied human activities, despite varying seasonal impacts that peak in fall, contribute marginal fraction (∼10–20% or less) to the interannual lake area decrease. Given that the TGD impacts on the total YP lake area and its seasonal variation are both under ∼5%, we also dismiss the speculation that the TGD might be responsible for evident downstream climate change by altering lake surface extent and thus open water evaporation. Nevertheless, anthropogenic impacts exhibited a strengthening trend during the past decade. Although the TGD has reached its full‐capacity water regulation, the negative impacts of human water consumption and TGD‐induced net channel erosion, which are already comparable to that of TGD's flow regulation, may continue to grow as crucial anthropogenic factors to future YP lake conservation. Key Points: The recent decadal lake decline in China's Yangtze Plain is a major result of climate variability, instead of direct human interventions The Three Gorges Dam (TGD) causes no major change in downstream climate given limited impacts on lake area and thus open water evaporation Impacts of human water consumption and Yangtze channel erosion are comparable to that of TGD flow regulation and may continue to grow